PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, KINERJA KEUANGAN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA BEI - UMI KALSUM (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
ABSTRACT The purpose of this study is to examine the effect of firm size, liquidity, financial performance and debt policy on corporate value in banking companies in Indonesia Stock Exchange. The population in this study are all banking companies listed on the Indonesia Stock Exchange, with a period of research from 2010 to 2013, amounting to 30 banking companies. The sample selected by using purposive sampling method amounting to 11 banking companies, with the technique of hypothesis testing research using multiple analysis techniques and test moderating the absolute difference. The result of the research proves partially that firm size, and financial performance have positive and significant influence to firm value, while liquidity have positive and insignificant effect to firm value and debt policy has negative and insignificant effect to firm value. Simultaneously shows that firm size, liquidity, financial performance, and debt policy have a positive and significant influence on firm value. Keywords: firm size (Size), liquidity (CR), financial performance (ROA), debt policy (DER), and firm value (PBV).